Rehabilitation in Industry - LeBlond, Wilfrid (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1953)
SummaryVocational rehabilitation in industry is more and more important; this article intends to cover the social and economic aspects of this problem. There are two factors in rehabilitation: the first, purely medical (prevention, medical and surgical treatments), concerns industrial medicine and the second, medico-social, consists of directing and counselling the handicapped worker. Rehabilitation has brought to the disabled person his recovery as a citizen, as a worker and as a father of a family.